The effects of group composition and fractionalization in a public goods game - Pablo Lucas; Angela C.M. de Oliveira; Sheheryar Banuri (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Behavioural economics highlights the role of social preferences in economic decisions. Further, populations are heterogeneous; suggesting that group composition may impact the ability to sustain voluntary public goods contributions. This parallels research in public economics where fractionalization negatively impacts provision. We conduct agent-based simulations of contributions in a public goods game, varying group composition and the weight individuals place on their beliefs versus their underlying social preference type. We then examine the effect of each of these factors on contributions. We find fractionalization in social preference types negatively impacts provision, even controlling for the share of types in a group.
Keywords: C63; D03; H41; I3; 330; social preferences; agent-based simulation; group composition; beliefs; Neue politische Ökonomie; Soziale Wohlfahrtsfunktion